Solder paste
The novel solder paste, featuring solder particles with a planar surface and a flux, addresses the issue of suboptimal wetting and spreading in existing solder pastes, resulting in improved connection reliability and reduced flux residue.
Patent Information
- Application Number
- JP2025021205
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-01-30
- Filing Date
- 2025-02-13
- Publication Date
- 2025-04-30
AI Technical Summary
Existing solder pastes lack optimal wetting and spreading properties, which affects the reliability of conductive connections in electronic devices.
A novel solder paste is developed, comprising solder particles with a planar portion on their surface, combined with a flux, which enhances wetting and spreading properties.
The novel solder paste exhibits improved wetting and spreading properties, leading to enhanced reliability of conductive connections and reduced flux residue, which minimizes ion migration and improves insulation reliability.
Smart Images

Figure 2025069454000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a solder paste. [Background technology]
[0002] Conventionally, the use of solder particles has been considered as conductive particles to be mixed into anisotropic conductive materials such as anisotropic conductive films, anisotropic conductive pastes, etc. For example, Patent Document 1 describes a conductive paste containing a thermosetting component and a plurality of solder particles that have been subjected to a specific surface treatment. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2016-76494 A Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to provide a novel solder paste. [Means for solving the problem]
[0005] One aspect of the present invention relates to a solder paste including solder particles and a flux, the solder particles having a flat portion on a part of their surface.
[0006] In one embodiment, the solder particles may have an average particle size of 1 to 30 μm and a CV value of 20% or less.
[0007] In one embodiment, the ratio (A / B) of the diameter A of the flat portion to the diameter B of the solder particle may satisfy the following formula. 0.01
[0008] In one aspect, when a quadrilateral circumscribing the projection image of the solder particles is created by two pairs of parallel lines, X and Y (where Y < X) may satisfy the following formula for the distances between opposite sides. 0.8 < Y / X < 1.0
[0009] In one aspect, the solder particles may contain at least one selected from the group consisting of tin, tin alloys, indium, and indium alloys.
[0010] In one aspect, the solder particles may contain at least one tin alloy selected from the group consisting of In-Sn alloys, In-Sn-Ag alloys, In-Bi alloys, Sn-Au alloys, Sn-Bi alloys, Sn-Bi-Ag alloys, Sn-Ag-Cu alloys, and Sn-Cu alloys.
Advantages of the Invention
[0011] According to the present invention, a novel solder paste is provided. By using solder particles having a flat portion on a part of the surface, a solder paste excellent in wetting spreadability can be obtained.
Brief Description of the Drawings
[0012] [Figure 1] FIG. 1 is a diagram schematically showing an example of solder particles. [Diagram 2] FIG. 2 is a diagram showing the distances X and Y (where Y ≤ X) between opposite sides when a quadrilateral circumscribing the projection image of the solder particles is created by two pairs of parallel lines. [Diagram 3] FIG. 3(a) is a plan view schematically showing an example of a substrate, and FIG. 3(b) is a cross-sectional view taken along line IIIb-IIIb shown in FIG. 3(a). [Figure 4] FIGS. 4(a) to (d) are cross-sectional views schematically showing examples of the cross-sectional shape of the concave portion of the substrate. [Diagram 5] FIG. 5 is a cross-sectional view schematically showing a state in which solder fine particles are accommodated in the concave portion of the substrate. [Figure 6]FIG. 6 is a cross-sectional view that illustrates a state in which solder particles are formed in recesses of a base. [Figure 7] FIG. 7 is an SEM image showing an example of a solder particle. [Figure 8] FIG. 8 is a diagram showing the results of the evaluation of wetting and spreading properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an embodiment of the present invention will be described. The present invention is not limited to the following embodiment. The materials exemplified below may be used alone or in combination of two or more types, unless otherwise specified. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified. A numerical range indicated using "~" indicates a range including the numerical values described before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in stages in this specification, the upper limit or lower limit of a numerical range of a certain stage may be replaced by the upper limit or lower limit of a numerical range of another stage. In the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced by the value shown in the example.
[0014] <Solder paste> The solder paste according to the present embodiment contains solder particles and flux, and may further contain a thermosetting component and other components.
[0015] (solder particles) The solder particles have a flat portion on a part of their surface. The details of the solder particles and the method for producing the same will be described later.
[0016] The content of the solder particles may be 1% by mass or more, 2% by mass or more, 10% by mass or more, 20% by mass or more, or 30% by mass or more, based on the total mass of the solder paste. The content may be 99% by mass or less, 90% by mass or less, or 85% by mass or less, based on the total mass of the solder paste. When the content of the solder particles is within the above range, it becomes easier to arrange the solder particles on the electrodes and also easier to arrange a large number of solder particles between the electrodes, which tends to improve the reliability of conduction.
[0017] (Flux) Examples of the flux include compounds that are generally used for solder joints, etc., such as zinc chloride, a mixture of zinc chloride and an inorganic halide, a mixture of zinc chloride and an inorganic acid, a molten salt, phosphoric acid, a derivative of phosphoric acid, an organic halide, hydrazine, an organic acid, rosin, etc. These fluxes may be used alone or in combination of two or more.
[0018] The molten salt may be ammonium chloride or the like. The organic acid may be lactic acid, citric acid, stearic acid, glutamic acid, glutaric acid or the like. The rosin may be activated rosin, non-activated rosin or the like. More specifically, the rosin may be rosins containing abietic acid as the main component. The flux is preferably rosins, and more preferably abietic acid. The use of these fluxes further increases the reliability of conduction between the electrodes.
[0019] The melting point of the flux may be 50°C or more, 70°C or more, or 80°C or more. The melting point may be 200°C or less, 160°C or less, 150°C or less, or 140°C or less. When the melting point of the flux is within the above range, the flux effect is easily exerted, and the solder particles tend to be efficiently arranged on the electrodes. For example, examples of fluxes having a melting point within the above range include dicarboxylic acids such as succinic acid (melting point 186°C), glutaric acid (melting point 96°C), adipic acid (melting point 152°C), pimelic acid (melting point 104°C), and suberic acid (melting point 142°C), benzoic acid (melting point 122°C), and malic acid (melting point 130°C).
[0020] As the flux, an organic acid having a hydroxyl group and a carboxyl group can be used. Aliphatic dihydroxycarboxylic acids are preferred because they efficiently remove the oxide film on the surface of the solder particles and provide good joint reliability. Examples of such acids include tartaric acid, 2,2-bis(hydroxymethyl)propionic acid, 2,2-bis(hydroxymethyl)butanoic acid, and 2,2-bis(hydroxymethyl)pentanoic acid.
[0021] The flux may not only be contained in the solder paste, but also adhered to the surfaces of the solder particles.
[0022] The flux content may be 0.5% by mass or more based on the total mass of the solder paste. The flux content may be 30% by mass or less, or 25% by mass or less based on the total mass of the solder paste. When the flux content is within the above range, an oxide film is unlikely to form on the surfaces of the solder and electrodes, and the oxide film formed on the surfaces of the solder and electrodes can be easily and effectively removed.
[0023] (thermosetting component) The thermosetting component may include a thermosetting compound and a thermosetting agent. Examples of the thermosetting compound include an oxetane compound, an epoxy compound, an episulfide compound, a (meth)acrylic compound, a phenol compound, an amino compound, an unsaturated polyester compound, a polyurethane compound, a silicone compound, and a polyimide compound.
[0024] The content of the thermosetting compound may be 10% by mass or more, 40% by mass or more, or 50% by mass or more based on the total mass of the solder paste, and may be 99% by mass or less, 98% by mass or less, 90% by mass or less, or 80% by mass or less based on the total mass of the solder paste.
[0025] Examples of the heat curing agent include imidazole curing agents, amine curing agents, phenolic curing agents, polythiol curing agents, acid anhydrides, thermal cationic initiators, thermal radical generators, etc. These heat curing agents may be used alone or in combination of two or more.
[0026] From the viewpoint of facilitating rapid hardening of the solder paste at low temperatures, imidazole hardeners, polythiol hardeners, amine hardeners, etc. can be used as the heat hardener. From the viewpoint of storage stability, a latent heat hardener can be used. As the latent hardener, a latent imidazole hardener, a latent polythiol hardener, a latent amine hardener, etc. can be used.
[0027] The reaction initiation temperature of the thermosetting agent may be 50° C. or more, 70° C. or more, or 80° C. or more. The reaction initiation temperature may be 250° C. or less, 200° C. or less, 150° C. or less, or 140° C. or less. When the reaction initiation temperature of the thermosetting agent is within the above range, the solder particles are likely to be efficiently arranged on the electrodes. In this specification, the reaction initiation temperature of the thermosetting agent refers to the temperature at which the rise of the exothermic peak begins in DSC.
[0028] The content of the thermosetting agent may be 0.01 parts by mass or more, or 1 part by mass or more, relative to 100 parts by mass of the thermosetting compound. The content may be 200 parts by mass or less, 100 parts by mass or less, or 75 parts by mass or less. When the content of the thermosetting agent is within the above range, the solder paste is easily cured, and after curing, excess thermosetting agent that is not involved in curing is unlikely to remain, and the heat resistance of the cured product tends to be high.
[0029] (Other Ingredients) The solder paste may further contain an organic solvent, a thixotropy control agent, a coupling agent, a reactive diluent, and the like, as necessary.
[0030] <Solder particles> The solder particles according to this embodiment have a flat surface on a part of the surface. In this case, the surface other than the flat surface is preferably spherical crown-shaped. That is, the solder particles may have a flat surface and a curved surface part of the spherical crown. When an anisotropic conductive material is obtained using such solder particles, it is possible to realize excellent conductive reliability and insulating reliability. The reason for this will be explained below.
[0031] First, the flat surface of the solder particle contacts the electrode, thereby ensuring a large contact area between the flat surface and the electrode. For example, when connecting an electrode made of a material that the solder easily spreads on and an electrode made of a material that the solder does not easily spread on, the flat surface of the solder particle can be adjusted to be disposed on the latter electrode side, thereby enabling the connection between the two electrodes to be suitably performed.
[0032] In addition, the larger the contact area between the solder particles and the electrode, the easier it is for the solder to spread. For example, as a method for making the solder particles arranged on the electrode (substrate) wet and spread to the electrode, there is a method of applying flux to the solder particles themselves or the electrode in advance, and dissolving the solder particles by reflow (heating). In this case, if the oxide film of the solder particles is thick or the flux is weak, the solder is difficult to spread if the contact area between the solder particles and the electrode is small. On the other hand, if there is a flat part on a part of the surface of the solder particles, the contact area between the electrode and the solder particles becomes large, and the solder tends to spread easily. This is presumably because, when the oxide film is being removed, if the electrode and the solder particle surface come into contact, the thinned oxide film cracks, and the melted solder and flux flow, making it easier to remove the oxide film. In this way, if the contact area between the solder particles and the electrode is large, the number of contact points between the electrode and the solder particle surface increases, and the timing of wetting and spreading is accelerated, making it easier to wet and spread. In addition, since the solder particles are easily wetted and spread, the amount of flux can be reduced, and the occurrence of ion migration due to flux residue can be suppressed.
[0033] Furthermore, since the solder particles having a flat surface have good seating properties, when the solder particles are arranged on the electrodes so that the flat surface contacts the electrodes, the solder particles are unlikely to become displaced from their stable shape. In other words, it is easy to prevent the solder particles from rolling out of the space between the electrodes before reflow, which can cause a decrease in reliability of electrical continuity between opposing electrodes and a decrease in reliability of insulation between adjacent electrodes.
[0034] FIG. 1 is a diagram showing a schematic diagram of an example of a solder particle 1 according to the present embodiment. As shown in FIG. 1, the solder particle 1 has a shape in which a flat portion 11 of diameter A is formed on a part of the surface of a sphere having a diameter B. From the viewpoint of realizing excellent conductivity reliability and insulation reliability, the ratio (A / B) of the diameter A of the flat portion to the diameter B of the solder particle 1 is set to, for example, more than 0.01 and less than 1.0 (0.01 Specifically, any particle is observed with a scanning electron microscope and an image is taken. From the image obtained, the diameter B of the solder particle and the diameter A of the flat surface are measured and the A / B of the particle is calculated. This procedure is performed on 300 solder particles and the average value is calculated to be the A / B of the solder particle.
[0035] The solder particles 1 may have an average particle diameter of 1 to 30 μm and a CV value of 20% or less. Such solder particles have both a small average particle diameter and a narrow particle size distribution, and can be suitably used as conductive particles for anisotropic conductive materials with high conductive and insulating reliability.
[0036] The average particle size of the solder particles is not particularly limited as long as it is within the above range, but is preferably 30 μm or less, more preferably 25 μm or less, and even more preferably 20 μm or less. The average particle size of the solder particles is preferably 1 μm or more, more preferably 2 μm or more, and even more preferably 4 μm or more.
[0037] The average particle size of the solder particles can be measured using various methods suited to the size. For example, dynamic light scattering, laser diffraction, centrifugal sedimentation, electrical sensing zone method, resonance mass measurement method, etc. can be used. Furthermore, a method can be used to measure the particle size from images obtained by an optical microscope, an electron microscope, etc. Specific devices include a flow type particle image analyzer, a microtrack, a Coulter counter, etc.
[0038] From the perspective of achieving better conductive reliability and insulation reliability, the C.V. value of the solder particles is preferably 20% or less, more preferably 10% or less, still more preferably 7% or less, and most preferably 5% or less. Also, the lower limit of the C.V. value of the solder particles is not particularly limited. For example, the C.V. value of the solder particles may be 1% or more, or may be 2% or more.
[0039] The C.V. value of the solder particles is calculated by multiplying the value obtained by dividing the standard deviation of the particle size measured by the aforementioned method by the average particle size by 100.
[0040] When a rectangle circumscribing the projection image of the solder particles is created by two pairs of parallel lines, when the distances between the opposing sides are X and Y (where Y < X), the ratio of Y to X (Y / X) may be greater than 0.8 and less than 1.0 (0.8 < Y / X < 1.0), or may be 0.81 to 0.99 or 0.81 to 0.95. Such solder particles can be said to be particles closer to a perfect sphere. When the solder particles are accommodated again in the concave portion 62 of the substrate 60, if the solder particles are close to a spherical shape, there is a tendency to be easily accommodated. Also, because the solder particles are close to a perfect sphere, when electrically connecting between a plurality of opposing electrodes via the solder particles, unevenness in contact between the solder particles and the electrodes is less likely to occur, and a stable connection tends to be obtained. Also, when producing a conductive film or paste in which the solder particles are dispersed in a resin material, high dispersibility is obtained, and dispersion stability during production tends to be obtained. Furthermore, when using a film or paste in which the solder particles are dispersed in a resin material for connection between electrodes, even if the solder particles rotate in the resin, if the solder particles are spherical, when viewed in the projection image, the projected areas of the solder particles are close to each other. Therefore, there is a tendency to easily obtain a stable electrical connection with less variation when connecting the electrodes. From the above perspectives, the circularity of the solder particles (the ratio r / R of the radii of two concentric circles (the radius r of the minimum circumscribed circle and the radius R of the maximum inscribed circle) of the solder particles) may be 0.85 or more, or may be 0.90 or more.
[0041] FIG. 2 is a diagram showing distances X and Y (where Y < X) between opposite sides when a quadrilateral circumscribing the projection image of solder particles is created by two pairs of parallel lines. For example, any particle is observed with a scanning electron microscope to obtain a projection image. For the obtained projection image, two pairs of parallel lines are drawn. One pair of parallel lines is arranged at the position where the distance between the parallel lines is minimized, and the other pair of parallel lines is arranged at the position where the distance between the parallel lines is maximized, and Y / X of the particle is obtained. This operation is performed on 300 solder particles to calculate the average value, which is taken as Y / X of the solder particles.
[0042] The solder particles may contain tin or a tin alloy. As the tin alloy, for example, In-Sn alloy, In-Sn-Ag alloy, Sn-Au alloy, Sn-Bi alloy, Sn-Bi-Ag alloy, Sn-Ag-Cu alloy, Sn-Cu alloy, etc. can be used. Specific examples of these tin alloys are as follows. · In-Sn (In 52 mass%, Bi 48 mass%, melting point 118°C) · In-Sn-Ag (In 20 mass%, Sn 77.2 mass%, Ag 2.8 mass%, melting point 175°C) · Sn-Bi (Sn 43 mass%, Bi 57 mass%, melting point 138°C) · Sn-Bi-Ag (Sn 42 mass%, Bi 57 mass%, Ag 1 mass%, melting point 139°C) · Sn-Ag-Cu (Sn 96.5 mass%, Ag 3 mass%, Cu 0.5 mass%, melting point 217°C) · Sn-Cu (Sn 99.3 mass%, Cu 0.7 mass%, melting point 227°C) · Sn-Au (Sn 21.0 mass%, Au 79.0 mass%, melting point 278°C) The solder particles may contain indium or an indium alloy. As the indium alloy, for example, In-Bi alloy, In-Ag alloy, etc. can be used. Specific examples of these indium alloys are as follows. · In-Bi (In 66.3 mass%, Bi 33.7 mass%, melting point 72°C) · In-Bi (In 33.0 mass%, Bi 67.0 mass%, melting point 109°C) In-Ag (In 97.0% by mass, Ag 3.0% by mass, melting point 145°C)
[0043] The above tin alloy or indium alloy can be selected depending on the application of the solder particles (temperature during use), etc. For example, when the solder particles are used for low-temperature fusion, an In-Sn alloy or an Sn-Bi alloy can be used, and in this case, fusion can be performed at 150°C or less. When a material with a high melting point such as an Sn-Ag-Cu alloy or an Sn-Cu alloy is used, high reliability can be maintained even after exposure to high temperatures.
[0044] The solder particles may contain one or more elements selected from Ag, Cu, Ni, Bi, Zn, Pd, Pb, Au, P, and B. Of these elements, Ag or Cu may be contained for the following reasons: When the solder particles contain Ag or Cu, the melting point of the solder particles can be lowered to about 220°C, and the bonding strength with the electrodes is further improved, making it easier to obtain better electrical connection reliability.
[0045] The Cu content of the solder particles is, for example, 0.05 to 10 mass%, and may be 0.1 to 5 mass% or 0.2 to 3 mass%. When the Cu content is 0.05 mass% or more, better solder connection reliability is easily achieved. When the Cu content is 10 mass% or less, the solder particles tend to have a low melting point and excellent wettability, and as a result, the connection reliability of the joints formed by the solder particles tends to be good.
[0046] The Ag content of the solder particles is, for example, 0.05 to 10 mass%, and may be 0.1 to 5 mass% or 0.2 to 3 mass%. When the Ag content is 0.05 mass% or more, better solder connection reliability is easily achieved. Also, when the Ag oil content is 10 mass% or less, the solder particles tend to have a low melting point and excellent wettability, and as a result, the connection reliability of the joints formed by the solder particles tends to be good.
[0047] The use of the solder particles is not particularly limited, and for example, they can be suitably used as conductive particles for anisotropic conductive materials. They can also be suitably used for applications such as electrically connecting electrodes together in a ball grid array connection method (BGA connection) that is widely used in the mounting of semiconductor integrated circuits, sealing or sealing parts such as MEMS, brazing, and spacers for controlling height and gap. In other words, the solder particles can be used in general applications where solder has been used in the past.
[0048] <Method of manufacturing solder particles> The method for manufacturing the solder particles according to the present embodiment is not particularly limited, but an example of the manufacturing method will be described below. For example, the solder particles according to the present embodiment can be manufactured by a method for manufacturing solder particles including a preparation step of preparing a base having a plurality of recesses and solder particles, a housing step of housing at least some of the solder particles in the recesses of the base, and a fusion step of fusing the solder particles housed in the recesses to form solder particles inside the recesses. According to this manufacturing method, solder particles having a flat portion on a part of the surface are manufactured.
[0049] Hereinafter, the method for producing the solder particles will be described with reference to FIGS.
[0050] First, solder particles and a base 60 for accommodating the solder particles are prepared. Fig. 3(a) is a plan view showing a schematic example of the base 60, and Fig. 3(b) is a cross-sectional view taken along line IIIb-IIIb shown in Fig. 3(a). The base 60 shown in Fig. 3(a) has a plurality of recesses 62. The recesses 62 may be regularly arranged in a predetermined pattern.
[0051] The recess 62 of the base 60 is preferably formed in a tapered shape with an opening area expanding from the bottom 62a of the recess 62 toward the surface 60a of the base 60. That is, as shown in Fig. 3, the width of the bottom 62a of the recess 62 (width a in Fig. 3) is preferably narrower than the width of the opening on the surface 60a of the recess 62 (width b in Fig. 3). The size of the recess 62 (width a, width b, volume, taper angle, depth, etc.) may be set according to the size of the desired solder particles.
[0052] The shape of the recess 62 may be a shape other than the shape shown in Fig. 3. For example, the shape of the opening in the surface 60a of the recess 62 may be an ellipse, a triangle, a rectangle, a polygon, etc., other than the circle as shown in Fig. 3.
[0053] The shape of the recess 62 in a cross section perpendicular to the surface 60a may be, for example, a shape as shown in FIG. 4. FIGS. 4(a) to (d) are cross-sectional views that typically show examples of the cross-sectional shapes of the recesses of the base. The bottom surface of each of the cross-sectional shapes shown in FIGS. 4(a) to (d) is flat. This forms a flat portion on a part of the surface of the solder particle. In addition, in each of the cross-sectional shapes shown in FIGS. 4(a) to (d), the width (width b) of the opening of the recess 62 on the surface 60a is the maximum width in the cross-sectional shape. This makes it easier to remove the solder particles formed in the recess 62, improving workability.
[0054] Materials that can be used to form the base 60 include inorganic materials such as silicon, various ceramics, glass, and metals such as stainless steel, as well as organic materials such as various resins. Of these, the base 60 is preferably made of a heat-resistant material that does not change at the melting temperature of the solder particles. The recesses 62 of the base 60 can be formed by known methods such as photolithography, imprinting, mechanical processing, electron beam processing, and radiation processing.
[0055] The solder particles prepared in the preparation step may include particles having a particle diameter smaller than the width (width b) of the opening in surface 60a of recess 62, and preferably include more particles having a particle diameter smaller than width b. For example, the solder particles preferably have a D10 particle diameter in the particle size distribution smaller than width b, more preferably a D30 particle diameter in the particle size distribution smaller than width b, and even more preferably a D50 particle diameter in the particle size distribution smaller than width b.
[0056] The particle size distribution of the solder particles can be measured using various methods suited to the size. For example, dynamic light scattering, laser diffraction, centrifugal sedimentation, electrical sensing zone method, resonance mass measurement method, etc. can be used. Furthermore, a method can be used to measure the particle size from images obtained by an optical microscope, an electron microscope, etc. Specific devices include a flow type particle image analyzer, a microtrack, a Coulter counter, etc.
[0057] Although the CV value of the solder particles prepared in the preparation step is not particularly limited, a high CV value is preferable from the viewpoint of improving the filling property of the combination of large and small particles into the recesses 62. For example, the CV value of the solder particles may exceed 20%, is preferably 25% or more, and is more preferably 30% or more.
[0058] The CV value of the solder fine particles is calculated by dividing the standard deviation of the particle diameter measured by the above-mentioned method by the average particle diameter (D50 particle diameter) and multiplying the result by 100.
[0059] The solder particles may contain tin or a tin alloy. Examples of the tin alloy include an In-Sn alloy, an In-Sn-Ag alloy, an Sn-Au alloy, an Sn-Bi alloy, an Sn-Bi-Ag alloy, an Sn-Ag-Cu alloy, and an Sn-Cu alloy. Specific examples of these tin alloys include the following: In-Sn (In 52% by mass, Bi 48% by mass, melting point 118°C) ·In-Sn-Ag (In20% by mass, Sn77.2% by mass, Ag2.8% by mass, melting point 175℃) Sn-Bi (Sn 43% by mass, Bi 57% by mass, melting point 138°C) · Sn-Bi-Ag (Sn 42% by mass, Bi 57% by mass, Ag 1% by mass, melting point 139°C) · Sn-Ag-Cu (Sn 96.5% by mass, Ag 3% by mass, Cu 0.5% by mass, melting point 217°C) Sn-Cu (Sn 99.3% by mass, Cu 0.7% by mass, melting point 227°C) ·Sn-Au (Sn21.0% by mass, Au79.0% by mass, melting point 278℃) The solder particles may contain indium or an indium alloy. Examples of the indium alloy include an In-Bi alloy and an In-Ag alloy. Specific examples of these indium alloys include the following. In-Bi (In 66.3 mass%, Bi 33.7 mass%, melting point 72°C) In-Bi (In 33.0 mass%, Bi 67.0 mass%, melting point 109°C) In-Ag (In 97.0% by mass, Ag 3.0% by mass, melting point 145°C)
[0060] The above tin alloy or indium alloy can be selected depending on the application of the solder particles (temperature during use), etc. For example, when it is desired to obtain solder particles for use in low-temperature fusion, an In-Sn alloy or an Sn-Bi alloy can be used, and in this case, solder particles that can be fused at 150° C. or less can be obtained. When a material with a high melting point, such as an Sn-Ag-Cu alloy or an Sn-Cu alloy, is used, solder particles that can maintain high reliability even after being left at high temperatures can be obtained.
[0061] The solder fine particles may contain one or more elements selected from Ag, Cu, Ni, Bi, Zn, Pd, Pb, Au, P, and B. Of these elements, Ag or Cu may be contained for the following reasons: When the solder fine particles contain Ag or Cu, the melting point of the resulting solder particles can be lowered to about 220°C, and good electrical reliability can be obtained by obtaining solder particles with excellent bonding strength with the electrodes.
[0062] The Cu content of the solder particles is, for example, 0.05 to 10 mass%, and may be 0.1 to 5 mass% or 0.2 to 3 mass%. When the Cu content is 0.05 mass% or more, solder particles that can achieve good solder connection reliability are easily obtained. When the Cu content is 10 mass% or less, solder particles that have a low melting point and excellent wettability are easily obtained, and as a result, the connection reliability of the joints formed by the solder particles is easily good.
[0063] The Ag content of the solder particles is, for example, 0.05 to 10 mass%, and may be 0.1 to 5 mass% or 0.2 to 3 mass%. If the Ag content is 0.05 mass% or more, it is easy to obtain solder particles that can achieve good solder connection reliability. Also, if the Ag oil content is 10 mass% or less, it is easy to obtain solder particles that have a low melting point and excellent wettability, and as a result, the connection reliability of the joints formed by the solder particles is easy to be good.
[0064] In the accommodation step, the solder particles prepared in the preparation step are accommodated in each of the recesses 62 of the base 60. The accommodation step may be a step in which all of the solder particles prepared in the preparation step are accommodated in the recesses 62, or a step in which only a portion of the solder particles prepared in the preparation step (for example, solder particles smaller than the opening width b of the recesses 62) are accommodated in the recesses 62.
[0065] Fig. 5 is a cross-sectional view that shows a schematic state in which solder particles 111 are accommodated in recesses 62 of base 60. As shown in Fig. 5, a plurality of solder particles 111 are accommodated in each of a plurality of recesses 62.
[0066] The amount of solder particles 111 accommodated in recess 62 is, for example, preferably 20% or more, more preferably 30% or more, even more preferably 50% or more, and most preferably 60% or more of the volume of recess 62. This reduces variation in the amount accommodated, making it easier to obtain solder particles with a smaller particle size distribution.
[0067] The method of storing the solder particles in the recesses 62 is not particularly limited. The storing method may be either a dry method or a wet method. For example, the solder particles prepared in the preparation step are placed on the base 60, and a squeegee is used to rub the surface 60a of the base 60, thereby removing excess solder particles and storing sufficient solder particles in the recesses 62. If the width b of the opening of the recesses 62 is greater than the depth of the recesses 62, the solder particles may protrude from the opening of the recesses 62. If a squeegee is used, the solder particles protruding from the opening of the recesses 62 are removed. Other methods for removing excess solder particles include blowing compressed air or rubbing the surface 60a of the substrate 60 with a nonwoven fabric or a bundle of fibers. These methods are preferable for handling solder particles that are easily deformed because they exert a weaker physical force than a squeegee. These methods also make it possible to leave the solder particles protruding from the opening of the recess 62 inside the recess.
[0068] The fusion process is a process in which the solder particles 111 contained in the recesses 62 are fused to form solder particles 1 inside the recesses 62. FIG. 6 is a cross-sectional view that shows a schematic state in which the solder particles 1 are formed in the recesses 62 of the base 60. The solder particles 111 contained in the recesses 62 are unified by melting, and become spherical due to surface tension. At this time, at the contact portion with the bottom 62a of the recesses 62, the molten solder follows the bottom 62a to form a flat portion 11. As a result, the formed solder particle 1 has a shape having a flat portion 11 on part of its surface.
[0069] FIG. 1 is a view of the solder particle 1 as viewed from the side opposite to the opening of the recess 62 in FIG.
[0070] As a method for melting the solder particles 111 accommodated in the recess 62, there is a method of heating the solder particles 111 to a temperature equal to or higher than the melting point of the solder. The solder particles 111 may not melt, wet, or spread even when heated to a temperature equal to or higher than the melting point due to the influence of an oxide film. For this reason, the solder particles 111 can be melted, wet, spread, and unified by exposing the solder particles 111 to a reducing atmosphere, removing the surface oxide film of the solder particles 111, and then heating the solder particles 111 to a temperature equal to or higher than the melting point of the solder particles 111. In addition, it is preferable to melt the solder particles 111 in a reducing atmosphere. By heating the solder particles 111 to a temperature equal to or higher than the melting point of the solder particles 111 and creating a reducing atmosphere, the oxide film on the surface of the solder particles 111 is reduced, and the melting, wet, spread, and unification of the solder particles 111 can be efficiently promoted.
[0071] The method for creating a reducing atmosphere is not particularly limited as long as the above-mentioned effects can be obtained, and examples of the method include a method using hydrogen gas, hydrogen radicals, formic acid gas, etc. For example, the solder particles 111 can be melted in a reducing atmosphere by using a hydrogen reduction furnace, a hydrogen radical reduction furnace, a formic acid reduction furnace, or a conveyor furnace or continuous furnace thereof. These devices may be equipped with a heating device, a chamber for filling an inert gas (nitrogen, argon, etc.), a mechanism for evacuating the chamber, etc., in the furnace, which makes it easier to control the reducing gas. In addition, if the chamber can be evacuated, voids can be removed by reducing the pressure after the solder particles 111 are melted and unified, and solder particles 1 with even more excellent connection stability can be obtained.
[0072] The profile of the reduction of the solder particles 111, the melting conditions, the temperature, the adjustment of the atmosphere in the furnace, etc. may be appropriately set in consideration of the melting point, particle size, recess size, and material of the base 60 of the solder particles 111 of the solder particles 111. For example, the base 60 having the recesses filled with the solder particles 111 is inserted into a furnace, and after evacuation, a reducing gas is introduced to fill the furnace with the reducing gas, the surface oxide film of the solder particles 111 is removed, and the reducing gas is removed by evacuation, and then the furnace is heated to a temperature equal to or higher than the melting point of the solder particles 111 to melt and coalesce the solder particles to form solder particles in the recesses 62. After that, nitrogen gas is filled and the temperature in the furnace is returned to room temperature to obtain the solder particles 1. Also, for example, the base 60 with the solder particles 111 filled in the recesses is inserted into a furnace, and after evacuation, reducing gas is introduced to fill the furnace with the reducing gas, the solder particles 111 are heated by an in-furnace heater to remove the surface oxide film of the solder particles 111, and then the reducing gas is removed by evacuation, and then the solder particles 111 are heated to a temperature equal to or higher than the melting point thereof to melt and coalesce the solder particles to form solder particles in the recesses 62, and then nitrogen gas is filled in and the temperature inside the furnace is returned to room temperature to obtain the solder particles 1. Heating the solder particles in a reducing atmosphere has the advantage of increasing the reducing power and making it easier to remove the surface oxide film of the solder particles.
[0073] Furthermore, for example, the base 60 with the solder particles 111 filled in the recesses is inserted into a furnace, and after evacuation, reducing gas is introduced to fill the furnace with the reducing gas, and the base 60 is heated by an in-furnace heater to above the melting point of the solder particles 111, the oxide film on the surface of the solder particles 111 is removed by reduction while at the same time the solder particles are melted and unified to form solder particles in the recesses 62, the reducing gas is removed by evacuation, and the voids in the solder particles are further reduced, after which nitrogen gas is filled and the temperature inside the furnace is returned to room temperature to obtain the solder particles 1. In this case, the temperature inside the furnace only needs to be increased and decreased once each, which has the advantage of allowing processing in a short time.
[0074] After the solder particles are formed in the recess 62, the furnace is once again made into a reducing atmosphere, and a process is added to remove any remaining surface oxide film, thereby reducing residues such as solder particles that remain unfused and parts of the oxide film that remain unfused.
[0075] When an atmospheric pressure conveyor furnace is used, the base 60 with the recesses filled with the solder particles 111 can be placed on a conveyor and passed through multiple zones in succession to obtain the solder particles 1. For example, the base 60 with the recesses filled with the solder particles 111 can be placed on a conveyor set to a constant speed, passed through a zone filled with an inert gas such as nitrogen or argon at a temperature lower than the melting point of the solder particles 111, then passed through a zone containing a reducing gas such as formic acid gas at a temperature lower than the melting point of the solder particles 111 to remove the surface oxide film of the solder particles 111, then passed through a zone filled with an inert gas such as nitrogen or argon at a temperature higher than the melting point of the solder particles 111 to melt and coalesce the solder particles 111, and then passed through a cooling zone filled with an inert gas such as nitrogen or argon to obtain the solder particles 1. For example, the base 60 with the solder particles 111 filled in the recesses is placed on a conveyer set at a constant speed, passed through a zone filled with an inert gas such as nitrogen or argon at a temperature equal to or higher than the melting point of the solder particles 111, and then passed through a zone where a reducing gas such as formic acid gas at a temperature equal to or higher than the melting point of the solder particles 111 is present, to remove the surface oxide film of the solder particles 111, melt and unify them, and then passed through a cooling zone filled with an inert gas such as nitrogen or argon to obtain solder particles 1. Since the conveyer furnace can perform processing at atmospheric pressure, it is also possible to continuously process a film-like material by roll-to-roll. For example, a continuous roll product of the base 60 with the solder particles 111 filled in the recesses is produced, and a roll unwinder is installed at the entrance side of the conveyer furnace and a roll winder is installed at the exit side of the conveyer furnace, and the base 60 is transported at a constant speed and passed through each zone in the conveyer furnace, thereby fusing the solder particles 111 filled in the recesses.
[0076] The formed solder particles 1 are removed from the recesses 62, recovered, and used to prepare a solder paste. Fig. 7 is an SEM image showing an example of a solder particle thus obtained. The solder particles 1 may be transported, stored, etc., in the state where they are contained in the recesses 62 of the base 60.
[0077] The manufacturing method of this embodiment can form solder particles of uniform size regardless of the material and shape of the solder particles. For example, indium-based solder can be deposited by plating, but it is difficult to deposit in a particulate form, and it is soft and difficult to handle. However, in the manufacturing method of this embodiment, indium-based solder particles are used as a raw material, so that indium-based solder particles having a uniform particle size can be easily manufactured. In addition, since the formed solder particles 1 can be handled in a state where they are accommodated in the recesses 62 of the base 60, they can be transported and stored without being deformed. Furthermore, since the formed solder particles 1 are simply accommodated in the recesses 62 of the base 60, they can be easily taken out, and they can be collected and surface-treated without being deformed.
[0078] Furthermore, the solder particles 111 may have a large variation in particle size distribution or may have an irregular shape, and as long as they can be contained within the recesses 62, they can be used as a raw material in the manufacturing method of this embodiment.
[0079] Furthermore, in the manufacturing method of this embodiment, the shape of the recesses 62 of the base 60 can be freely designed by lithography, imprinting, electron beam processing, radiation processing, mechanical processing, etc. Since the size of the solder particles 1 depends on the amount of solder fine particles 111 contained in the recesses 62, in the manufacturing method of this embodiment, the size of the solder particles 1 can be freely designed by designing the recesses 62.
[0080] Although the preferred embodiments of the present invention have been described above, the present invention is not limited to the above-described embodiments. EXAMPLES
[0081] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0082] <Preparation of solder particles> [Example 1] (Step a1: Classification of solder particles) 100g of Sn-Bi solder particles (5N Plus, melting point 139℃, Type 8) were immersed in distilled water, ultrasonically dispersed, and then left to stand, and the solder particles floating in the supernatant were collected. This process was repeated to collect 10g of solder particles. The average particle size of the obtained solder particles was 1.0μm, and the CV value was 42%. (Step b1: Arrangement on a substrate) A substrate (polyimide film, 100 μm thick) was prepared that had multiple recesses with an opening diameter of 1.2 μmφ, a bottom diameter of 1.0 μmφ, and a depth of 1.0 μm (the bottom diameter of 1.0 μmφ is located in the center of the opening diameter of 1.2 μmφ when the opening is viewed from above). The multiple recesses were regularly arranged at intervals of 1.0 μm. The solder particles (average particle diameter 1.0 μm, CV value 42%) obtained in step a were placed in the recesses of the substrate. The surface of the substrate on which the recesses were formed was rubbed with a slightly adhesive roller to remove excess solder particles, and a substrate was obtained in which the solder particles were placed only in the recesses. (Step c1: Formation of solder particles) The substrate with the solder particles placed in the recesses in step b1 was placed in a hydrogen reduction furnace, and after evacuation, hydrogen gas was introduced into the furnace to fill it with hydrogen. The furnace was then kept at 280°C for 20 minutes, after which it was evacuated again, nitrogen was introduced to return the pressure to atmospheric pressure, and the temperature inside the furnace was then lowered to room temperature to form the solder particles.
[0083] In addition, solder particles were recovered from the concave portion by tapping the substrate that had undergone step c1 from the back side of the concave portion. The obtained solder particles were observed by the following method. The obtained solder particles were placed on a conductive tape fixed to the surface of a pedestal for scanning electron microscope (SEM) observation, and the SEM observation pedestal was tapped on a stainless steel plate with a thickness of 5 mm to spread the solder particles evenly on the conductive tape. Then, compressed nitrogen gas was blown onto the surface of the conductive tape to fix the solder particles in a single layer on the conductive tape. The observation results are shown in FIG. 7. FIG. 7 is an SEM image of the solder particles obtained in Example 1. As shown in the figure, the obtained solder particles had a shape in which a flat portion was formed on a part of the surface of the sphere. In addition, the solder particles obtained in other examples also had the same shape.
[0084] <Evaluation of Solder Particles> After attaching a conductive tape so as to face the concave portion of the substrate that had undergone step c1 and then peeling it off, an observation sample in which the flat portions of the solder particles were arranged in parallel to the surface of the conductive tape was obtained. After performing Pt sputtering on the surface of the observation sample where the solder particles were arranged, SEM observation was performed. 300 solder particles were observed, and the average diameter B (average particle diameter), average diameter A of the flat portion, C.V. value, circularity, A / B, and Y / X of the solder particles were calculated. The results are shown in Table 1. Circularity: The ratio r / R of the radii of two concentric circles (radius r of the minimum circumscribed circle and radius R of the maximum inscribed circle) of the solder particle. A / B: The ratio of the diameter A of the flat portion to the diameter B of the solder particle. Y / X: When a quadrangle circumscribing the projection image of the solder particle is created by two pairs of parallel lines, the ratio of Y to X when the distances between the opposing sides are X and Y (where Y < X).
[0085] [Examples 2 to 12] Solder particles were produced in the same manner as in Example 1 except that the concave portion size was changed as shown in Table 1, and the solder particles were evaluated.
[0086] <Preparation of Solder Paste> [Production Example 1] 16.0 parts by mass of YL980 (trade name of bisphenol A type epoxy resin manufactured by Mitsubishi Chemical Corporation), 0.8 parts by mass of 2P4MHZ-PW (trade name of imidazole compound manufactured by Shikoku Kasei Co., Ltd.), and 3.2 parts by mass of adipic acid as a flux activator were mixed, and the mixture was passed through a triple roll three times to prepare an adhesive component.
[0087] Next, 80 parts by mass of Sn-Bi solder particles having flat surfaces formed on part of the surface of the spheres produced in Example 1 were added to 20 parts by mass of the adhesive component, and the resulting mixture was stirred and kneaded using a planetary mixer and subjected to a degassing treatment at 500 Pa or less for 10 minutes to obtain a solder paste.
[0088] [Examples 2-12] A solder paste was prepared in the same manner as in Preparation Example 1, except that the Sn-Bi solder particles obtained in Examples 2 to 12, each of which had a flat portion formed on a part of the spherical surface, were used.
[0089] [Preparation Example 13] 16.7 parts by mass of YL980 (trade name of bisphenol A type epoxy resin manufactured by Mitsubishi Chemical Corporation), 0.8 parts by mass of 2P4MHZ-PW (trade name of imidazole compound manufactured by Shikoku Kasei Co., Ltd.), and 2.5 parts by mass of adipic acid as a flux activator were mixed, and the mixture was passed through a triple roll three times to prepare an adhesive component.
[0090] Next, 80 parts by mass of Sn-Bi solder particles having a flat surface formed on part of the spherical surface, as prepared in Example 5, were added to 20 parts by mass of the adhesive component, and the resulting mixture was stirred and kneaded using a planetary mixer and subjected to a degassing treatment at 500 Pa or less for 10 minutes to obtain a solder paste.
[0091] [Comparative Preparation Example 1] A solder paste was prepared in the same manner as in Preparation Example 1, except that SnBi solder particles ("ST-3" manufactured by Mitsui Kinzoku Co., Ltd.) without flat surfaces were used instead of the Sn-Bi solder particles with flat surfaces formed on part of the spherical surfaces. The average particle size of the SnBi solder particles was 4 μm, and the CV value was 31%.
[0092] [Comparative Preparation Example 2] A solder paste was prepared in the same manner as in Preparation Example 1, except that SnBi solder particles without flat surfaces ("Type-4" manufactured by Mitsui Kinzoku Co., Ltd.) were used instead of the Sn-Bi solder particles with flat surfaces formed on part of the spherical surface. The average particle size of the SnBi solder particles was 26 μm, and the CV value was 25%.
[0093] [Comparative Preparation Example 3] 15.4 parts by mass of YL980 (trade name of bisphenol A type epoxy resin manufactured by Mitsubishi Chemical Corporation), 0.8 parts by mass of 2P4MHZ-PW (trade name of imidazole compound manufactured by Shikoku Kasei Co., Ltd.), and 3.9 parts by mass of adipic acid as a flux activator were mixed, and the mixture was passed through a triple roll three times to prepare an adhesive component.
[0094] Next, 80 parts by mass of SnBi solder particles ("ST-3" manufactured by Mitsui Kinzoku Co., Ltd.) not having flat surfaces as described above were added to 20 parts by mass of the adhesive component, and the resulting mixture was stirred and kneaded with a planetary mixer and subjected to a degassing treatment at 500 Pa or less for 10 minutes to obtain a solder paste.
[0095] [Comparative Preparation Example 4] 16.7 parts by mass of YL980 (trade name of bisphenol A type epoxy resin manufactured by Mitsubishi Chemical Corporation), 0.8 parts by mass of 2P4MHZ-PW (trade name of imidazole compound manufactured by Shikoku Kasei Co., Ltd.), and 2.5 parts by mass of adipic acid as a flux activator were mixed, and the mixture was passed through a triple roll three times to prepare an adhesive component.
[0096] Next, 80 parts by mass of SnBi solder particles ("ST-3" manufactured by Mitsui Kinzoku Co., Ltd.) not having flat surfaces as described above were added to 20 parts by mass of the adhesive component, and the resulting mixture was stirred and kneaded with a planetary mixer and subjected to a degassing treatment at 500 Pa or less for 10 minutes to obtain a solder paste.
[0097] The properties of the solder pastes of the above Preparation Examples and Comparative Preparation Examples were measured by the following methods. The results are summarized in Table 2.
[0098] (1) Evaluation of adhesive strength 0.5 mg of solder paste was applied onto a silver-plated copper plate (10 mm x 15 mm, thickness: 0.20 mm), and a rectangular flat tin-plated copper chip (2 mm x 2 mm, thickness: 0.25 mm) was laminated on top of it, and then a test piece was obtained by applying a heat history of 150°C for 10 minutes using a hot plate. The shear strength of this test piece was measured at 25°C using a bond tester (DAGE, 2400) under the conditions of a shear speed of 500 μm / sec and a clearance of 100 μm.
[0099] (2) Temperature cycle test A rectangular flat thin FR4 board measuring 100 mm x 50 mm x 0.5 mm was prepared, which had two adjacent copper foil lands (0.2 mm x 0.4 mm) and a distance between the copper foil lands of 100 μm. Next, a solder paste was printed on the copper foil lands using a metal mask (thickness 100 μm, opening dimensions 0.2 mm x 0.3 mm), and a small chip resistor (0.2 mm x 0.4 mm) with an electrode distance of 100 μm was mounted. The same thermal history as in (1) above was applied to this component-mounted board to obtain a test board for evaluating TCT resistance. After checking the initial resistance of this test board using a simple tester, it was put into a thermal shock tester (1 cycle: held at -55 ° C for 30 minutes, heated to 125 ° C in 5 minutes, held at 125 ° C for 30 minutes, cooled to -55 ° C in 5 minutes), and the connection resistance was measured. The evaluation of TCT resistance was based on the number of cycles that showed a resistance change rate within ±10% of the initial resistance.
[0100] (3) Insulation resistance test After measuring the insulation resistance of the component-mounted board prepared in the same manner as in (2) above, a migration test (temperature 60°C, humidity 90%, 50 V applied) was carried out. The migration resistance was evaluated by measuring the insulation resistance of the board by 10 9 The test time at which the resistance was below Ω was used as an index.
[0101] All of Preparation Examples 1 to 13 exhibited good adhesive strength, and showed good results in both the temperature cycle test and the insulation resistance test.
[0102] In Comparative Examples 1 and 2, it was confirmed that the adhesive strength was significantly decreased and the temperature cycle resistance was decreased.
[0103] In Comparative Example 3, although an improvement in connectivity due to an increase in the flux component was observed, a decrease in insulation due to migration was confirmed.
[0104] In Comparative Example 4, although an improvement in insulation reliability was observed due to the reduction in the flux component, a decrease in connection strength due to a decrease in solder wettability and a decrease in temperature cycle resistance were confirmed.
[0105] Although solder particles with an average particle size of 4 μm were used in Preparation Example 5 and Comparative Preparation Example 1, differences were observed in the connection strength and connection reliability, which are affected by the wettability and spreadability of the solder particles. Preparation Example 5 and Comparative Preparation Example 1 were evaluated for wettability and spreadability.
[0106] A predetermined amount of solder paste was printed on rolled copper foil (10 mm × 15 mm, thickness: 0.04 mm) using a printing metal mask (opening: 5 mm × 5 mm, thickness: 0.1 mm), and the solder paste was subjected to a heat history of 150°C for 3 minutes using a hot plate to evaluate the wettability and spreadability. The wettability and spreadability evaluation results are shown in Figure 8.
[0107] Figure 8(a) shows the wetting and spreading properties of Production Example 5. It can be seen that the ink quickly spreads onto the copper foil while maintaining its square shape after printing.
[0108] 8(b) is a diagram showing the wetting and spreading properties of Comparative Preparation Example 1. It can be seen that the wetting and spreading properties on the copper foil were poor and the wetting and spreading properties were uneven.
[0109] [Table 1]
[0110] [Table 2] [Explanation of symbols]
[0111] 1...solder particle, 11...flat portion, 111...solder fine particle, 60...base, 60a...surface, 62...recess, 62a...bottom.
Claims
1. The solder paste includes solder particles and a flux. The solder paste, wherein the solder particles have a flat portion on a part of their surface.
2. 2. The solder paste according to claim 1, wherein the solder particles have an average particle size of 1 to 30 μm and a CV value of 20% or less.
3. 3. The solder paste according to claim 1, wherein a ratio (A / B) of a diameter A of the flat portion to a diameter B of the solder particle satisfies the following formula: 0.01<A / B<1.0
4. The solder paste according to any one of claims 1 to 3, wherein when a rectangle circumscribing a projected image of the solder particle is created by two pairs of parallel lines, and the distances between opposing sides are X and Y (where Y<X), X and Y satisfy the following formula: 0.8<Y / X<1.0
5. The solder paste according to any one of claims 1 to 4, wherein the solder particles contain at least one selected from the group consisting of tin, a tin alloy, indium, and an indium alloy.
6. 6. The solder paste of claim 5, wherein the solder particles include at least one tin alloy selected from the group consisting of an In-Sn alloy, an In-Sn-Ag alloy, an In-Bi alloy, a Sn-Au alloy, a Sn-Bi alloy, a Sn-Bi-Ag alloy, a Sn-Ag-Cu alloy, and a Sn-Cu alloy.
Citation Information
Patent Citations
Metal powder and paste thereof
JP1989184201A
Method for forming metal ball
JP1993023887A
Terminal connection structure, terminal connection method, manufacture of conductive particle, and manufacturing board
JP1993082934A
Solder powder and solder paste
JP2010036234A
Method for manufacturing mold for producing solder ball and method for producing solder ball
JP2014058147A